EVALUASI PENGGUNAAN SISTEM AKUNTANSI INSTANSI BERBASIS AKRUAL (SAIBA) DI PENGADILAN NEGERI MUNGKID - Nurlaila, Afifah; Fitri Ariesta Susilo, Ghina (SEKOLAH PASCASARJANA PRESS, 2021)
This study aims to evaluate the accrual-based institutional accounting system (SAIBA) in the Mungkid District Court. The research method is qualitative research with descriptive research method. Data collection techniques in this study used interview, documentation and observation techniques. The results of the study revealed that the Mungkid District Court in preparing financial reports has use an accrual-based institutional accounting system (SAIBA) starting in 2015. In implementing SAIBA, the District Court of Mungkid complies with Government Regulation No. 71 of 2010 concerning government accounting standards.